Lawyer disciplinary processes: an empirical study of solicitors' misconduct cases in England and Wales in 2015. (September 2019) - Boon, Andrew; Whyte, Avis
Abstract: The Legal Services Act 2007 effected major changes in the disciplinary system for solicitors in England and Wales. Both the practice regulator, the Solicitors Regulation Authority, and a disciplinary body, the Solicitors Disciplinary Tribunal, were reconstituted as independent bodies and given new powers. Our concern is the impact of the Act on the disciplinary system for solicitors. Examination of this issue involves consideration of changes to regulatory institutions and the mechanics of practice regulation. Drawing on Foucault's notion of governmentality, empirical evidence drawn from disciplinary cases handled by the Solicitors Disciplinary Tribunal and the Solicitors Regulation Authority in 2015 is used to explore potentially different conceptions of discipline informing the work of the regulatory institutions. The conclusion considers the implications of our findings for the future of the professional disciplinary system.